The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Environmental Health and Biomedicine 2011
DOI: 10.2495/ehr110331
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic organs for transplant and bio-mimic reactors for process intensification using nano-structured micro-porous materials

Abstract: In order to achieve Process Intensification through monolithic micro-reactors in bio-and chemical technology we examined the processing strategy in the human body, taking the liver as a typical organ. The macro-and micro-architectural structure can be mimicked by using nano-structured micro-porous polymers which were used as support in tissue engineering and bioprocess intensification. It was shown that these materials could be used as bone transplant and they are integrated into the body. Their integration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It must be indicated that expanded polystyrene beads are used in horticulture as a perlite substitute [ 57 ]. Furthermore, these PHP materials were also used as support for bacteria [ 18 ] and mammalian cells [ 16 , 17 , 31 ] in bioprocess intensification and were shown to have no adverse reaction in animals when they were used as bone graft [ 58 ]. Graft PHPs could not be distinguished from natural bone because bone cells migrated into the graft and even vascularised it [ 58 ].…”
Section: Environmental Impact and Sustainability Of Agro-process Intementioning
confidence: 99%
See 1 more Smart Citation
“…It must be indicated that expanded polystyrene beads are used in horticulture as a perlite substitute [ 57 ]. Furthermore, these PHP materials were also used as support for bacteria [ 18 ] and mammalian cells [ 16 , 17 , 31 ] in bioprocess intensification and were shown to have no adverse reaction in animals when they were used as bone graft [ 58 ]. Graft PHPs could not be distinguished from natural bone because bone cells migrated into the graft and even vascularised it [ 58 ].…”
Section: Environmental Impact and Sustainability Of Agro-process Intementioning
confidence: 99%
“…Furthermore, these PHP materials were also used as support for bacteria [ 18 ] and mammalian cells [ 16 , 17 , 31 ] in bioprocess intensification and were shown to have no adverse reaction in animals when they were used as bone graft [ 58 ]. Graft PHPs could not be distinguished from natural bone because bone cells migrated into the graft and even vascularised it [ 58 ]. In the absence of any discernible biodegradation of polystyrene, we can expect SRS media to remain in soil without being replenished periodically and therefore limiting the impact of any unforeseen adverse environmental impact.…”
Section: Environmental Impact and Sustainability Of Agro-process Intementioning
confidence: 99%
“…Each lobule is constructed around a central vein with rows of hepatocytes arranged in cellular plates radiating outwards, forming a roughly hexagonal pattern. The lobules are surrounded by multiple portal triads, which consist of a branch of the portal vein, a branch of the hepatic artery, and a tributary of the bile duct [14]. Hepatic plates are typically two cells thick and are separated by small bile canaliculi, which empty into bile ducts in the fibrous septa that separate adjacent liver lobules.…”
Section: Anatomy Of the Livermentioning
confidence: 99%
“…In diffusion-controlled processes or reactions, the reduction of the diffusion path is clearly a target for PI, which can be achieved by using reactors or catalysts with three levels of length scales, especially in gas phase reactions; (1) Macroscopic level for convective transfer, which is always necessary for industrial-scale application, (2) Nano level for mass transfer and (3) Microscopic level for reactor connectivity between the macroscopic and nano-scale levels of the reactor [2,3]. In fact, this concept already exists in physiological processes where mass transfer can take place through lipid bilayers, which can be further facilitated through neural control [153]. Chemical reactors modelled on physiological processes can have significant PI attributes when they are supplemented by structured catalysts operating at high temperatures and pressures in the presence of additional PI fields such as electric, plasma and microwave.…”
Section: Multi-reaction Zone Reactors (M-rzr) For Ammonia and Symbiot...mentioning
confidence: 99%